Facile Production of Biodiesel from Candlenut Oil (Aleurites moluccana L.) Using Photocatalytic Method by Nano Sized-ZnO Photocatalytic Agent Synthesized via Polyol Method - Hendro Juwono; Anisun Zakiyah; Riki Subagyo; Yuly Kusumawati (Universitas Gadjah Mada, 2023)
Biodiesel production from non-edible oil is an alternative way to reduce edible oil dependency and reduce the competition for feed and food. Candlenut oil (Aleurites moluccana L.) is one of the non-edible oils which can be used as feedstock for biodiesel production since they have a high oil content. Herein, the biodiesel production from candlenut oil has been conducted using zinc oxide (ZnO) synthesized by the polyol method. Polyol methods facilitated the formation of ZnO nanoparticles with various shapes, including spherical, rod, and hexagonal. Besides, ZnO showed a mesoporous characteristic, facilitating the conversion of fat fatty acid to fatty acid methyl ester (FAME) of 61%. Increasing ZnO dosage led to enhancing the FAME yield. Similarly, the FAME yield was also improved by increasing the reaction time. The results of esterification of candlenut oil and methanol yielded 70.76% FAME with 2% nano-ZnO polyol catalyst at 180 min reaction time at room temperature whilst being stirred constantly at 400 rpm. A good FAME conversion using ZnO at room temperature provides good information to produce biodiesel with a simple method. Apart from that, photocatalytic promoted transesterification at room temperature, which is beneficial for reducing energy consumption.